Dendrimers and Polyamino-Phenolic Ligands: Activity of New Molecules Against Legionella pneumophila Biofilms - Andreozzi, Elisa; Barbieri, Federica; Ottaviani, Maria F.; Giorgi, Luca; Bruscolini, Francesca; Manti, Anita; Battistelli, Michela; Sabatini, Luigia; Pianetti, Anna (Frontiers in Microbiology, 2016)
Legionnaires’ disease is a potentially fatal pneumonia caused by Legionella pneumophila, an aquatic bacterium often found within the biofilm niche. In man-made water systems microbial biofilms increase the resistance of legionella to disinfection, posing a significant threat to public health. Disinfection methods currently used in water systems have been shown to be ineffective against legionella over the long-term, allowing recolonization by the biofilm-protected microorganisms. In this study, the anti-biofilm activity of previously fabricated polyamino-phenolic ligands and polyamidoamine dendrimers was investigated against legionella mono-species and multi-species biofilms formed by L. pneumophila in association with other bacteria that can be found in tap water (Aeromonas hydrophila, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae). Bacterial ability to form biofilms was verified using a crystal violet colorimetric assay and testing cell viability by real-time quantitative PCR and Plate Count assay. The concentration of the chemicals tested as anti-biofilm agents was chosen based on cytotoxicity assays: the highest non-cytotoxic chemical concentration was used for biofilm inhibition assays, with dendrimer concentration ten-fold higher than polyamino-phenolic ligands. While Macrophen and Double Macrophen were the most active substances among polyamino-phenolic ligands, dendrimers were overall two-fold more effective than all other compounds with a reduction up to 85% and 73% of legionella and multi-species biofilms, respectively. Chemical interaction with matrix molecules is hypothesized, based on SEM images and considering the low or absent anti-microbial activity on planktonic bacteria showed by flow cytometry. These data suggest that the studied compounds, especially dendrimers, could be considered as novel molecules in the design of research projects aimed at the development of efficacious anti-biofilm disinfection treatments of water systems in order to minimize legionellosis outbreaks.